WAYS TO DEVELOP WRITTEN SPEECH IN STUDENTS WITH DYSLEXIA AND DYSGRAPHIA - Maxmudova Madinaxon Sobirxonovna; Mamadaliyeva Faridaxon Nabijon qizi (Bright Mind Publishing, 2025)
Through the article, you can get information about recommendations for the formation of readiness for written speech in children of primary school age with underdeveloped speech, a system of work aimed at creating a functional basis for written speech, directions and technologies for preventing written speech defects, as well as allowing for the rapid and effective mastery of written speech.
Keywords: Writing, speech, visual activity, phonemic perception, literacy training period, oral speech, phonemic perception, cognitive processes, abilities.